Molecular Analysis of SARS-CoV-2 Spike Protein-Induced Endothelial Cell Permeability and vWF Secretion - Venkat Kanamarlapudi (International Journal of Molecular Sciences, 2023)
Coronavirus disease COVID-19, which is caused by severe acute respiratory syndrome coronavirus SARS-CoV-2, has become a worldwide pandemic in recent years. In addition to being a respiratory disease, COVID-19 is a ‘vascular disease’ since it causes a leaky vascular barrier and increases blood clotting by elevating von Willebrand factor (vWF) levels in the blood. In this study, we analyzed in vitro how the SARS-CoV-2 spike protein S1 induces endothelial cell (EC) permeability and its vWF secretion, and the underlying molecular mechanism for it. We showed that the SARS-CoV-2 spike protein S1 receptor-binding domain (RBD) is sufficient to induce endothelial permeability and vWF-secretion through the angiotensin-converting enzyme (ACE)2 in an ADP-ribosylation factor (ARF)6 activation-dependent manner. However, the mutants, including those in South African and South Californian variants of SARS-CoV-2, in the spike protein did not affect its induced EC permeability and vWF secretion. In addition, we have identified a signaling cascade downstream of ACE2 for the SARS-CoV-2 spike protein-induced EC permeability and its vWF secretion by using pharmacological inhibitors. The knowledge gained from this study could be useful in developing novel drugs or repurposing existing drugs for treating infections of SARS-CoV-2, particularly those strains that respond poorly to the existing vaccines.